A comparison between the effectiveness of lycra and silon pressure garments for treatment of hypertrophic scar in burns - Bujang Safawi, Ehfa (2011)
Introduction Hypertrophic scarring after burns remains a major challenge for burn care providers. Pressure garments and silicone sheets have been the mainstay of hypertrophic scar treatment. This study was to compare the effectiveness of the traditional Lycra pressure garment and the silicone incorporated pressure garment (Silon) and also to determine patients’ satisfaction with pressure garment among burns patients in Hospital Universiti Sains Malaysia. Methodology This is was a two-phased study. Phase I was a retrospective study, which involved patients who were treated with the Lycra pressure garments from June 2007 until Jun 2009. Meanwhile, phase II was a prospective study, involving patients who were treated with the Silon pressure garments from June 2008 until June 2010. Demographic details collected included age, type and depth of burn, total burn surface area (TBSA) and cause of injury. The effectiveness of the treatment was determined based on the Vancouver Scar Scale score. Patients’ scars were assessed 2 weeks after complete wound healing, and every 4 months, for up to 1 year. Results Repeated measures ANOVA showed significant improvement in terms of scar vascularity, itch and pain within each study group (p < 0.05). However, there was no statistical difference between the two pressure garment groups (p > 0.05). Meanwhile, there was no significant difference within and between the 2 study groups in terms of scar height, pigmentation and pliability. Majority of the patient complained of itch, sweating, discomfort and tightness upon wearing the pressure garments. In addition to interfering with their daily activities, they also reported no improvement of their scar appearance. Nevertheless, they still believe that compliance with the treatment is of great importance in order to gain optimal result. Conclusion We cannot conclude that the combined pressure garment and silicone therapy (Silon) was more effective than the traditional pressure garment (Lycra). Hypertrophic scars following burns injuries can take up to 2 years to reach maturity. Thus, it is recommended that scars should be monitored and pressure garment treatment should be carried out for at least 2 years.